Estimation of the net energy and protein requirements for maintenance of male arctic foxes (Alopex lagopus) during the growth period1, 2. (26th October 2019) - Zhong, W; Mu, L L; Han, F F; Luo, G L; Zhang, X Y; Liu, K Y; Guo, X L; Yang, H M; Li, G Y
Abstract: The maintenance requirements of net energy and net protein were assumed to represent the most accurate and important values totally for the animal's utilization. The objective of this experiment was to determine the net energy and net protein requirements for maintenance of growing arctic foxes. The experiments was evaluated using regression models estimated from data collected by means of indirect calorimetry, nitrogen balance trials, and digestion and metabolism experiments. Thirty-six growing arctic foxes (3 487 ± 261.7 g) at the age of 85 days were randomly assigned to four groups with 9 animals in each group. Arctic foxes were fed a complete formula diet at four intake levels (100%, or 80%, 60%, and 40% of feed requirements) from 24 July 2017 to 23 September 2017. Arctic foxes in each treatment were kept individually in respiration chambers after 1-d adaptation at day 2 for a 3-d balance trial and then at day 5 followed by a 3-d fasting period. The metabolizable energy intake (MEI ), heat production in the fed state (HP ), and retained energy (RE ) of arctic foxes significantly decreased ( P < 0.01) as the feed intake level decreased. Fasting heat production (FHP) of arctic foxes was not influenced by feed intake level ( P > 0.05). The metabolizable energy maintenance requirement (ME m ) and net energy maintenance requirement (NEm ) estimated from the linear relationship between RE and MEI were 230 and 217 kJ/kg of body weight BW 0.75 /d, respectively. The MEm and NEm estimated by logarithmic regression of HP on MEI were 225 and 209 kJ/kg BW 0.75 /d, respectively. The net N maintenance requirement (NN m ) and net protein maintenance requirement (NP m ) estimated from the linear relationship between retained nitrogen (RN ) and daily nitrogen intake (NI ) were 179.6 mg/kg BW 0.75 /d and 1.123 g/kg BW 0.75 /d, respectively. It is concluded that NEm and NPm values obtained fill the net energy and protein requirements shortage, and provide the basic data for establishing the standard of nutrition demand of breeding arctic foxes in China.